Neoproterozoic–middle Paleozoic tectono-magmatic evolution of the Gorny Altai terrane, northwest of the Central Asian Orogenic Belt: Constraints from detrital zircon U–Pb and Hf-isotope studies - Chen M.; Min Sun; Buslov M.M.; Keda Cai; Zhao G.; Zheng J.; Rubanova E.S.; Voytishek E.E. (My University, 2015)
The Gorny Altai terrane (GA) is a key area in understanding the crustal evolution of the Central Asian Orogenic Belt (CAOB). This paper reports U–Pb and Hf-isotope data for detrital zircons from Cambrian to early Devonian sedimentary sequences to constrain their provenance, as well as the tectono-magmatic events and crustal growth in this region. Nearly all the detrital zircons are characterized by euhedral to subhedral morphology, high Th/U ratios (ca. 0.1–1.6) and typical oscillatory zoning, indicating a magmatic origin. The three samples fromtheGorny AltaiGroup (middle Cambrian to earlyOrdovician) yield detrital zircon populations that are composed predominantly of 530–464 Ma grains, followed by a subordinate group of 641–549 Ma old. The Silurian and Devonian samples exhibit similar major zircon populations (555–456 Ma and 525–463 Ma, respectively), but a signiﬁcant amount of additional 2431–772Ma zircons occur in the early Devonian sample. Our results suggest that detritus from the nearby Kuznetsk–Altai intra-oceanic island arc served as a unitary source for the Cambrian–Silurian sedimentary sequences, but older detritus from other sources added to the early Devonian sequence. The lowabundance of ca. 640–540Ma detrital zirconsmay testify that this island arcwas under a primitive stage in this period,whenmaﬁc volcanic rocks probably dominated. In contrast, the dominant population of ca. 530–470Ma zirconsmay indicate an increased amount of granitic rocks in the source area, suggesting that the Kuznetsk–Altai island arc possibly evolved into a mature one in the Cambrian to early Ordovician. The ca. 530–470 Ma detrital zircons are almost exclusively featured by positive εHf(t) values and have two-stage Hf model ages of ca. 1.40–0.45 Ga, indicating that the precursormagmaswere sourced predominantly fromheterogeneous juvenilematerials.We conclude that the lateNeoproterozoic to early Paleozoicmagmatismin the Kuznetsk–Altai arc made a signiﬁcant contribution to the crustal growth in the CAOB. The absence of middle Ordovician to early Devonian detrital zircons possibly implies that the area changed to a passive margin in the middle Ordovician. Of special signiﬁcance are the 2431–772 Ma zircons in the early Devonian sample, which are quite comparable to the Precambrian detrital zircons from the Altai–Mongolian terrane (AM) but distinct fromthose fromthe Siberian continent. This indicates that the AMis a plausible source for the 2431–772Ma zircons. Our data therefore imply that the GA possibly amalgamatedwith the AMbefore the early Devonian rather than in the late Devonian to early Carboniferous as previously suggested.
Keywords: Gorny Altai terrane; Kuznetsk–Altai island arc; Detrital zircons; Crustal evolution; Палеозой::Ордовикская; Палеозой::Кембрийская; Докембрий::Протерозой::Неопротерозойская; Paleozoic::Ordovician; Paleozoic::Cambrian; Precambrian::Proterozoic::Neoproterozoic